TINJAUAN LITERATUR SISTEMATIS: STATUS PERTUMBUHAN DAN PERKEMBANGAN ANAK PASCA COVID-19 - Herlina Febrianti; Dessie Wanda; Efa Apriyanti (PERSATUAN AHLI GIZI INDONESIA, 2023)
COVID-19 affects growth, development, and death. The objective of this article is to find out the growth and developmental status of children post-COVID-19. This systematic review uses the PICO search strategy through an online database. Obtained 11 articles based on inclusion criteria, reviewed using the Critical Appraisal Skills Programme tools to conclude. COVID-19 influences growth (obesity or overweight) and child development (a disorder of language, emotional, behavioral, and psychosocial development). The growth and development of children post-COVID-19 are influenced by sex, age, length of hospital stay, comorbidities, and illness severity. The stimulus for optimal growth and development in post-COVID-19 children can be provided through affection, stimulation, balanced nutrition with a variety of foods, hand washing with soap, adequate physical activity, and regular weight monitoring. Keywords: children, COVID-19, development, growth ABSTRAKCOVID-19 berpengaruh terhadap pertumbuhan, perkembangan, dan kematian. Artikel ini bertujuan untuk mengetahui status pertumbuhan dan perkembangan anak pasca COVID-19. Systematic review ini menggunakan strategi pencarian PICO melalui database online. Diperoleh 11 artikel berdasarkan kriteria inklusif, review menggunakan Critical Appraisal Skills Programme tools hingga disimpulkan. Hasil menunjukkan COVID-19 memberikan pengaruh terhadap pertumbuhan (obesitas, IMT (Indeks Massa Tubuh) berlebih) dan perkembangan anak (gangguan perkembangan bahasa, emosi, perilaku dan psikosial). Pertumbuhan dan perkembangan anak pasca COVID-19 dipengaruhi jenis kelamin, usia, lama rawat, komorbiditas dan tingkat keparahan. Stimulus untuk pertumbuhan dan perkembangan yang optimal pada anak pasca COVID-19 dapat melalui pemberian kasih sayang, stimulasi, gizi seimbang dengan jenis makanan yang bervariasi, cuci tangan menggunakan sabun, aktivitas fisik yang cukup, dan pemantauan berat badan secara rutin.Kata kunci: anak, COVID-19, perkembangan, pertumbuhan